A kinetic study of fusion burn waves in compressed deuterium–tritium and proton–boron plasmas - Lavell, Michael J.; Kish, Ayden J.; Sexton, Andrew T.; Evans, Eugene S.; Mohammad, Ibrahim; Gomez-Ramirez, Sara; Scullin, William; Borscz, Marcus; Pikuz, Sergey; Mehlhorn, Thomas A.; Tabak, Max; Ainsworth, Greg; et al. (Frontiers in Physics, 2024)
We present particle-in-cell simulations with Monte Carlo collisions of fusion burn waves in compressed deuterium-tritium and proton-boron plasmas. We study the energy balance in the one-dimensional expansion of a hot-spot by simulating Coulomb collisions, fusion reactions, and bremsstrahlung emission with a Monte Carlo model and inverse bremsstrahlung absorption using a new PIC model. This allows us to self-consistently capture the alpha particle heating and radiative losses in the expanding hot-spot and surrounding cold fuel. After verifying our model in a code-to-code comparison with both kinetic and fluid codes for the case of a deuterium-tritium hotspot, we simulate the expansion of a proton-boron hot-spot initialized at 200 keV and 1000 g/cm 3 .We demonstrate that the radiation model extracts energy from the electrons resulting in lower ion temperatures and slower burn wave propagation. Over the course of 10 ps, we find more energy is generated from p-11 B fusion reactions than lost due to bremsstrahlung radiation.